Offshore evidence for volcanic landslide post Last Glacial Maximum at sub-Antarctic Heard Island, southern Indian Ocean - Jodi M. Fox; Sally J. Watson; Trevor J. Falloon; Rebecca J. Carey; Joanne M. Whittaker; Erica A. Spain; Robert A. Duncan; Richard J. Arculus; Millard F. Coffin (Volcanica)
Heard Island, an active sub-Antarctic intraplate volcanic island on the Kerguelen Plateau, is mostly covered by glaciers. The amphitheatre shaped summit of the active volcanic centre, Big Ben (2813 m), has been interpreted to be the product of a significant volcanic landslide. Here we present the first offshore geomorphological and geological evidence supporting a volcanic landslide on Big Ben, including: (1) the seafloor to the southwest of Heard resembling a landslide deposit, covering at least 467 km2, (2) the spatial correlation between the onshore landslide scar and the offshore deposit and (3) the consistency in lithologies and compositions of rocks sampled from the deposit with the onshore in situ lithologies. 40Ar/39Ar geochronology constrains the maximum age of the volcanic landslide to 18.0 ± 1.4 ka, post the Last Glacial Maximum. Finally, we assess the risk of volcanic landslide at Heard Island in the future.